What are UFOs? [videorecording (DVD)] - Randall, Terri; Randall, Terri; Ehrmann, Jedd (PBS, 2025)
Unidentified Flying Objects have long captivated the imagination of the public, but for decades most scientists treated the subject as taboo. Now, these mysterious phenomena are moving out of the shadows and into the light, as NASA pledges to study them scientifically. So, what exactly does science have to say on the matter? This new NOVA investigation looks at the evidence from every angle, marshaling expert opinions from physicists, engineers, cosmologists, and others who are bringing new technologies and heightened rigor to solving these mysteries. How can new ground-based sensors and crowdsourcing of data help explain what military pilots and others have seen? Many of these sightings can be attributed to physical objects like balloons or drones, weather phenomena, or optical illusions, but others so far remain mysterious. What other potential explanations remain? Could they be the result of secret new technologies developed by other governments ₇ or our own? And what would it take for alien engineers to traverse vast distances to send probes or visit Earth from other solar systems?